Barbara F. Vucanovich : From Nevada to Congress, and Back Again - Vucanovich, Barbara F., 1921-2013 (Book collections on Project MUSE., 2005)
"Nevadan Barbara Vucanovich enjoyed a long, productive, and somewhat unlikely political career. After years as a wife, mother, businesswoman, community activist, and campaign volunteer, she increased her political involvement by serving as the northern Nevada manager of Paul Laxalt's several campaigns. In 1982, encouraged by Laxalt to run in Nevada's newly created Second Congressional District, she became a sixty-one-year-old first-time political candidate. She campaigned as a "tough grandmother" and became the first Nevada woman ever elected to a federal office." "Over the next fourteen years, Congressman (the title she preferred) Vucanovich worked tirelessly to advance the interests of her state and the conservative ideals of the Republican Party. In this detailed memoir, she reflects on her political career and the long road that led to it. Her lively accounts of campaigning and office-holding offer a rare insider's view of the day-to-day realities of a politician's life - the excitement and exhaustion of hard-fought campaigns; the endless cross-country commutes to maintain contact with constituents; the inner workings of Congress as bills are written, debated, and voted on. Her descriptions of campaigning in Nevada, with its sparse and largely rural population, tell us more about the true nature of politics in the Silver State than any number of academic studies, and her profiles of other politicians - from Reno city leaders to Nevada state and national officeholders to her congressional colleagues to presidents of the United States - offer insight into the personalities and politics of some of the most important American political figures of the past half-century. She gives us an insider's chronicle of the "Gingrich Revolution" that brought the Republicans into control of Congress, and her account of her efforts on behalf of such women's issues as breast cancer research and child care demonstrates that her activism and dedication extended far beyond Nevada."--Jacket